Translation termination mechanism studied by solution state NMR - Li, Yan (2012)
Translation termination occurs when one of three stop-codons (UAA, UGA, or UAG) in mRNA reaches the ribosomal A site. In eukaryotes, class-I release factor (eRF1) directly recognizes all three stop-codons in the A site on the small ribosomal subunit and stimulates peptide release. N-domain of eRF1 plays an important role in the stop-codon recognition; however, the precise mechanism of stop-codon discrimination by eRF1 remains obscure, hindering drug development targeting aberrations at translation termination. Through comparison of the solution structure of Q122FM(Y)F126 mutant, the Y125F mutant of eRF1 N-domain and the wild type eRF1 N-domain which are determined, we built the correlation between the structure and the stop-codon recognition and found that the conserved GTS loop adopts alternate conformations. We propose that structural variability in the GTS loop may underline the switching between omnipotency and unipotency of eRF1, implying the direct access of the GTS loop to the stop-codon. Also, we proposed a model of eRF1 bound to the A site of eukaryotic ribosome.